Balance method of integrated control of mine water removal by the volumes and mineralization rate within the Ingulets river basin - P. I. Kovalchuk; V. V. Stetsenko; Н. A. Balykhina; V. P. Kovalchuk; O. S. Demchuk (Меліорація і водне господарство, 2021)
The balance method of determining the share of Kryvyi Rig Basin enterprises by the accumulated volume of mine water in the storage pond was considered. The balance method of participation of mining enterprises by the shares of mineral substances was formalized. An integrated approach of the control of water removal into the storage pond when using linear convolution of two balance equations by both the share of water volumes and the mineralization rate in the water discharges of enterprises was developed. It takes into account the choice of equity participation in mine water removal by economic and environmental criteria.